Estimation of resistance allele frequencies to Cry1A.105 and Cry2Ab2 in the corn earworm (Lepidoptera: Noctuidae) with F2 isolines generated from a mass-mating method. (November 2022) - Yu, Wenbo; Head, Graham P.; Price, Paula; Brown, Sebe; Cook, Don; Ni, Xinzhi; Reay-Jones, Francis P.F.; Dimase, Marcelo; Huang, Fangneng
Abstract: The corn earworm/bollworm, Helicoverpa zea (Boddie), in the United States is targeted by transgenic corn and cotton expressing Bacillus thuringiensis (Bt) proteins. Previous studies have shown that resistance to Cry1A/Cry2A Bt corn has occurred in the field. In this study, we established 103 F2 isolines by mass-mating of H. zea populations collected during 2018 and 2019 in four southeastern U.S. states: Louisiana, Mississippi, Georgia, and South Carolina. Dissection of mated females showed that at least 92.7% of the isolines were originated from single matings, suggesting that the applied mass-mating method is a suitable approach to establish H. zea F2 isolines. F2 screen showed that resistance allele frequencies in these isolines were high to the two Bt proteins expressed in MON 89034 corn hybrids, averaging 0.405 for Cry1A.105 and 0.330 for Cry2Ab2. The observed high resistance allele frequencies confirm that resistance to Cry1A/Cry2A in the insect is common in the southeastern region. In addition, the F2 screen showed that resistance allele frequencies (0.490 for Cry1A.105 and 0.541 for Cry2Ab2) in the populations collected in 2019 were significantly greater than the frequencies (0.312 for Cry1A.105 and 0.081 for Cry2Ab2) in the populations collected in 2018, indicating that selection for the Cry resistance was likely still ongoing in the field. Information generated from this study is useful to assess resistance risk, refine resistance modeling, and improve IRM programs to mitigate Cry resistance in H. zea for the sustainable use of Bt crop technology in the United States. Highlights: 103 F2 isolines were established by mass-mating of H. zea collected during 2018 and 2019 in four southeastern U.S. states. Dissection of mated females showed that almost all isolines were originated from single matings. The applied mass-mating method is a suitable approach to establish H. zea F2 isolines. F2 screen showed that resistance allele frequencies in these isolines were high to Cry1A.105 and Cry2Ab2. The results confirm that resistance to Cry1A/Cry2A in H. zea is common in the southeastern U.S. region.